THE INFLUENCE OF SERVICE QUALITY AND MEDICAL STAFF ATTITUDE ON THE SATISFACTION LEVEL OF OUTPATIENT BPJS PATIENTS AT RSUD BUMIAYU, BREBES REGENCY - Mohammad Fajar Mukharram; Vip Paramarta; Rukhiyat Syahidin (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
This study aims to analyze the effect of service quality and medical staff attitudes on the satisfaction level of BPJS outpatient patients at RSUD Bumiayu, Brebes Regency. The research background is based on the existence of patient complaints regarding service quality and medical staff attitudes, which are perceived as suboptimal. The study employed a quantitative method with descriptive and verificative approaches. Primary data were obtained from questionnaires distributed to 281 BPJS outpatient respondents, while secondary data were collected from hospital records. Service quality variables were measured using the five SERVQUAL dimensions (tangible, reliability, responsiveness, assurance, empathy), while medical staff attitudes were assessed through three dimensions (cognitive, affective, behavioral). Multiple linear regression analysis revealed that both service quality and medical staff attitudes significantly influence patient satisfaction, both partially and simultaneously. These findings highlight the importance of improving service quality and fostering positive medical staff attitudes to enhance BPJS outpatient satisfaction at RSUD Bumiayu.